Association of frequency of television watching with overweight and obesity among women of reproductive age in India: Evidence from a nationally representative study - Gupta, Rajat Das; Haider, Shams Shabab; Sutradhar, Ipsita; Hashan, Mohammad Rashidul; Sajal, Ibrahim Hossain; Hasan, Mehedi; Haider, Mohammad Rifat; Sarker, Malabika (PLOS ONE, 2022)
This article was published in The Plos One [ © 2019 Das Gupta et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pone.0221758. The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0221758